EFEKTIFITAS JALAN KAKI 30 MENIT TERHADAP NILAI GULA DARAH PADA PASIEN DIABETES MELLITUS TIPE II DI DESA KARANGSARI KECAMATAN KARANGANYAR KABUPATEN PEKALONGAN - Isrofah, Isrofah; Nurhayati, Nurhayati; Angkasa, Projo (Universitas Muhammadiyah Magelang, 2017)
Background: Diabetes mellitus  is a disease with  increase  in blood  sugar  levels. Blood sugar control can be done by exercise such as walking 30 minutes.  Objective: aimed determine the effect walking 30 minutes to blood sugar value of type  II  diabetes mellitus  patients  in  the Karangsari  village Karanganyar  district Ppekalongan regency. Methods: Design of this research used quasi-experimental. Samples were type II diabetes  mellitus  patients  in  the  Karangsari  village  Karanganyar  district Pekalongan  regency  as  many  as  20  peoples.  The  sampling  technique  used accidental sampling. The research instrument were standard laboratory instrument and stop watch. Analysis of the data used wilcoxon test.  Result: there were 13 people (65 %) with normal blood sugar before walking 30 minutes  and  13 pepole  (65 %)  with  abnormal  blood  sugar  after  walking  30 minute. There was not the effect walking 30 minutes to blood sugar value of type II  diabetes  mellitus  patients  in  the  Karangsari  village  Karanganyar  district Pekalongan Regency with p value equal to 0.180> 0.05.  Suggestion: Nurses more improve the provision of information about the benefits of walking 30 minutes to diabetes mellitus patients to control blood sugar levels.